Internationalization as myth, ceremony and doxa in higher education. The case of the Nordic countries between centre and periphery - Kazimierz Musiał (Taylor & Francis Group, 2023)
ABSTRACTThe article deals with the validation of the internationalization imperative in higher education institutions (HEIs) of the Nordic countries. I focus on both the goals and motives behind activities supporting internationalization, but also on the manner of their habitualization and institutionalization in the practice of academic administration and organizational management. The issue of legitimization of institutional changes is addressed by means of the rationalized myths that create durable dispositions for specific practices, changes in procedures and attitudes in a given socio-political setting. I draw on empirical examples that include practical solutions and strategies developed under the conditions of semiperipheral positionality of the Nordic states. This perspective makes their internationalization policies an interesting frame of reference for other countries and the paper concludes by pointing to the latest trends that can serve either as an inspiration or a warning for other states. The Nordic countries offer an example of how institutionalizing the 'strategic gains' narrative from globalization may lead to a recalibration of an earlier knowledge regime along with attempts to change centre-periphery relations, including the reframing of priorities and rationalities of different stakeholders in higher education.